Circumpolar projections of Antarctic krill growth potential - Devi Veytia; Stuart Corney; Klaus Meiners; So Kawaguchi; Murphy, EJ; Sophie Bestley (2020)
Antarctic krill is a key species of important Southern Ocean food webs, yet how changes in ocean temperature and primary production may impact their habitat quality remains poorly understood. We provide a circumpolar assessment of the robustness of krill growth habitat to climate change by coupling an empirical krill growth model with projections from a weighted subset of IPCC Earth system models. We find that 85% of the study area experienced only a moderate change in relative gross growth potential (± 20%) by 2100. However, a temporal shift in seasonal timings of habitat quality may cause disjunctions between krill’s biological timings and the future environment. Regions likely to experience habitat quality decline or retreat are concentrated near the northern limits of krill distribution and in the Amundsen–Bellingshausen seas region during autumn, meaning habitat will likely shift to higher latitudes in these areas.